Weaned pigs experimentally infected with Salmonella display sexually dimorphic innate immune responses without affecting pathogen colonization patterns, ,. Issue 1 (1st February 2017) - Burdick Sanchez, Nicole C.; Broadway, Paul R.; Carroll, Jeffery A.; Gart, Elena V.; Bryan, Laura K.; Lawhon, Sara D.
Abstract: Sexually dimorphic innate immune responses have been observed in several species, but have not been studied in response to a live pathogen challenge in pigs. This study aimed to elucidate sexually dimorphic innate immune responses along with Salmonella translocation patterns in newly weaned pigs orally inoculated with Salmonella . Newly weaned pigs ( n = 8 gilts and 12 barrows; 6.2 ± 0.2 kg BW) were obtained from a commercial swine facility and were maintained in an environmentally-controlled facility in individual pens equipped with feeders and nipple waterers. Pigs were allowed ad libitum access to a commercial non-medicated starter ration and water throughout the study. On d 12 post-weaning, pigs were anesthetized to allow placement of a temperature measuring device in the abdominal cavity for measurement of intraperitoneal temperature (TEMP). On d 17, pigs were anesthetized and fitted with indwelling jugular vein catheters. On the following day (d 18), pigs were orally inoculated with 4.7x10 9 Salmonella typhimurium. Blood samples were collected at 0.5-h intervals from -2 to 8 h, and at 8-h intervals from 8 to 72 h post-challenge. Whole blood was analyzed for complete blood cell counts. Serum was isolated for measurement of cortisol. Following collection of the 72 h sample, pigs were humanely euthanized and tissues were collected for Salmonella isolation. There was a sex × time interaction ( P < 0.001) for TEMP such that gilts had a greater TEMP response to the Salmonella challenge compared to barrows. There was also a sex × time interaction ( P = 0.03) for serum cortisol with gilts having decreased cortisol at 16 h yet greater cortisol at 32 h than barrows. Barrows had greater total white blood cells (17.8 vs. 16.2 ± 0.4 10 3 cells/μL; P < 0.01; respectively) and neutrophils (7.8 vs. 6.1 ± 0.4 10 3 cells/μL; P < 0.01; respectively) than gilts. However, gilts had greater lymphocytes (9.6 vs. 9.0 ± 0.2 10 3 cells/μL; P = 0.05; respectively) than barrows. While immune parameters were influenced by sex, there was no effect of sex ( P > 0.05) on Salmonella concentrations from fecal shedding 3 d post-inoculation in the cecum, mesenteric and subiliac lymph nodes, liver, spleen, gallbladder, or kidney tissues. These data demonstrate that weaned gilts appear to produce a stronger acute phase response to a Salmonella challenge compared to barrows, without affecting the tissue translocation or shedding of Salmonella .